Implementasi Magang PKKM di Desa Bongo Kecamatan Batudaa Pantai Kabupaten Gorontalo - Lukman Pakaya (Jurnal Pelayanan Masyarakat, 2025)
The Liga 1 Independent Campus Competition Program (PKKM) is an initiative of the Ministry of Education, Culture, Research, and Technology which aims to provide opportunities for students to learn outside the classroom through structured internship activities. The Independent Learning Independent Campus (MBKM) internship program is designed to equip students with readiness to enter the business and industrial world (DUDI), as well as implement course theory through hands-on work practice in the field. The MBKM internship activity which was carried out in Bongo Village, Batudaa Pantai District, Gorontalo Regency, aimed to provide real experience to students in village financial management. Bongo Village was chosen as the location of the internship because of its reputation as the best village in the region. The intern students converted the courses that had been programmed with the practice of implementing the village financial system based on the Siskeudes application. Through this activity, students not only understand the theory of public financial management, but also gain technical and social skills in interacting with village officials and the community. The results of the internship activities show that students are able to understand and operate the Siskeudes system effectively. The knowledge and skills gained are expected to be implemented in nine other villages in Bone Bolango District, as a form of real contribution to more transparent and accountable village financial governance. This program proves that collaboration between universities and village governments can have a positive impact on human resource capacity building and village governance. Thus, MBKM internships are a strategic means in supporting the transformation of higher education that is relevant to the needs of the community and regional development.